Outside in: the matrix as a modifier of muscular dystrophy - Quattrocelli, Mattia (Biochim Biophys Acta, 2016)
Muscular dystrophies are genetic conditions leading to muscle degeneration and often, impaired regeneration. Duchenne Muscular Dystrophy is a prototypical form of muscular dystrophy, and like other forms of genetically inherited muscle diseases, pathological progression is variable. Variability in muscular dystrophy can arise from differences in the manner in which the primary mutation impacts the affected protein’s function; however, clinical heterogeneity also derives from secondary mutations in other genes that can enhance or reduce pathogenic features of disease. These genes, called genetic modifiers, regulate the pathophysiological context of dystrophic degeneration and regeneration. Understanding the mechanistic links between genetic modifiers and dystrophic progression sheds light on pathologic remodeling, and provides novel avenues to therapeutically intervene to reduce muscle degeneration. Based on targeted genetic approaches and unbiased genomewide screens, several modifiers have been identified for muscular dystrophy, including extracellular agonists of signaling cascades. This review will focus on identification and possible mechanisms of recently identified modifiers for muscular dystrophy, including osteopontin, latent TGFβ binding protein 4 (LTBP4) and Jagged1. Moreover, we will review the investigational approaches that aim to target modifier pathways and thereby counteract dystrophic muscle wasting.